Leydig cell tumor of testis in a child: An uncommon presentation - Madhumita Mukhopadhyay; Chhanda Das; Sucharita Sarkar; Biswanath Mukhopadhyay; Bedabrata Mukhopadhyay; Rishavdeb Patra (Wolters Kluwer Medknow Publications, 2017)
Leydig cell tumors (LCTs) are rare testicular tumors. Incidence is 1%-3% of all testicular neoplasms, bilateral in 10%. They are frequently hormonally active, leading to feminizing or virilizing syndromes. LCTs can be either pure or mixed with germ cell tumors or other sex cord-stromal tumors. Here, we are reporting a benign pure LCT in a 6-year-old boy presented with pseudopuberty.